An assessment of aesthetics and comfort for women's apparel products in terms of pattern design parameters. (April 2019) - Zhao, Yu; Song, Jing; Yu, Qiuyu; Mo, Yu; Liu, Zhen; Walton, Jonathan; Chen, Jie
The proper assessment of aesthetics and comfort is an important step before launching a new type of apparel. Most current works on this assessment are qualitative and hard to be applied in practical to improve apparel design. In this study, we proposed two quantitative mappings from pattern design parameters to degree of aesthetics and pattern design parameters to degree of comfort for assessing aesthetics and comfort of apparel, and particularly, women's pants have been investigated. Statistical analysis was employed in the mappings' development. An experiment was conducted as a validation for the mappings. Two major conclusions are drawn from this study. The first is that these mappings enable to extract a more advanced pattern for apparel design after the iterative pattern revision. The second is that these mappings are able to be digitalized and then the traditional method of observing feedbacks of aesthetics and comfort for an apparel product can be updated into a more efficient and low-cost one.